A CASE OF KETOGENIC DIET-INDUCED ELEVATED CHOLESTEROL - Ci, Goh Qing; Mustafa, Norlaila (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Weight management through exercise and dietary intervention has been shown to reduce cardiovascular risk. Here, we report a case of significant weight loss achieved through exercise and a ketogenic diet, resulting in a deranged lipid profile. CASE A 39-year-old female with underlying class 3 obesity and type 2 diabetes mellitus on metformin 500 mg BD was first seen in March 2022. Her weight was 153 kg and her BMI was 58.2 kg/m2 . Since then, she has diligently followed a strict ketogenic diet and exercised daily. She ate one meal a day, and her diet primarily consisted of meat, eggs, nuts, cheese and fresh cream. Over the past 18 months, she successfully lost 85 kg, and her BMI decreased to 25.6 kg/m2 . Notably, her body composition improved, and her diabetes went into remission. However, her lipid profile exhibited marked derangement. Physical examination revealed no significant abnormalities, and it was noteworthy that both her parents had a history of dyslipidaemia. In response to the deranged lipid profile, the patient was advised to discontinue her current dietary plan. Instead, a more balanced diet emphasizing lower fat content, higher fibre intake and appropriate carbohydrate levels was recommended. Additionally, she was initiated on atorvastatin in October 2023 to address the lipid abnormalities. Regular monitoring and follow-up appointments were scheduled to track her progress. CONCLUSION While intermittent fasting and the ketogenic diet can undoubtedly lead to desired weight loss, patients should be counselled and carefully monitored by their physicians. This case illustrates that much is still unknown about the impact of these diets.